RANCANG BANGUN REAKTOR BIOGAS DENGAN PENGADUK - Munazzirah, Munazzirah; Iswadi, Iswadi; Ihsan, Ihsan (JFT : Jurnal Fisika dan Terapannya, 2016)
This research aims to design and compare the results to the biogas reactor with a stirrer with a biogas reactor without a stirrer. The research has successfully designed a biogas reactor with a stirrer with a stirrer using a dynamo as a player with a capacity of 11 kg. From the results of tests performed 3 times a day for 9 days, had the highest pH value data obtained on day 5 is 7.5 to biogas reactor with a stirrer and a biogas reactor without a stirrer. For the measurement of temperature changes irregularly due to unfavorable weather conditions remain. For the production of biogas in the biogas reactor with a stirrer, began to be seen on day 5 with a value of 76.3 cmHg whereas the increase in biogas reactors without biogas agitator begins to form on day 7 with a 76.5 rise in value. This tool is used for testing samples of cow dung as a sample of the most nice and easy to obtain. Based on the results of research conducted, it can prove that the biogas reactor stirrer dngan able to produce biogas more quickly than the biogas reactor without a stirrer this was due to the substrate in the fermentation container tercempur homogeneously so that the bacteria is able to reproduce a whole.